Results of sea buckthorn breeding in the Southern Urals - A. A. Vasiliev; F. M. Gasimov; V. S. Ilyin (Труды по прикладной ботанике, генетике и селекции)
Cultivation of adaptive fruit and berry crop varieties ensures environmental sustainability of horticulture. In the period of 2016–2020, sea buckthorn cultivars developed in Chelyabinsk and the Altai were assessed for adaptability, environmental plasticity, and stability under the conditions of Chelyabinsk Province. Sea buckthorn cultivars of local breeding appeared most adapted to the conditions of the Southern Urals. Among them, 1 accession was of the intensive type: 18-42-41 (70,4 ц/га; bi = 1,51; Si 2 = 4,9); 9 cultivars combined environmental plasticity and stability: ‘Yantarnoye ozherelye’ (7.74 t/ha; bi = 0,89; Si 2 = 8,5), 18-41-27n (7.17 t/ha; bi = 1.09; Si 2 = 3.1), ‘Chelyabinskaya’ (7.07 t/ha; bi = 0.98; Si 2 = 7.1), 18-42-40n (7.07 t/ha; bi = 1.01; Si 2 = 12.0), ‘Koster’ (7.04 t/ha; bi = 1.06; Si 2 = 8.9), ‘Damskiye palchiki’ (6.88 t/ha; bi = 0.72; Si 2 = 1.1), ‘Karotinnaya’ (6.85 t/ha; bi = 0.92; Si 2 = 6.1), 18-6-22 (6.78 t/ha; bi = 0.83; Si 2 = 7.7), and 18-6-18n (6.75 t/ha; bi = 0.86; Si 2 = 3.9); and 6 accessions were of the neutral type: ‘Lisichka’ (6.91 t/ha; bi = 0.51; Si 2 = 15.9), 18-2-38 (6.78 t/ha; bi = 0.49; Si 2 = 3,6), ‘Fantaziya’ (6.69 t/ha; bi = 0.69; Si 2 = 0.7), ‘Solnyshko’ (6.66 t/ha; bi = 0.69; Si 2 = 3.0), ‘Ryzhik’ (6.46 t/ha; bi = 0.63; Si 2 = 3.6), and 18-40-27 (6.40 t/ha; bi = 0.52; Si 2 = 4.4). The studied sea buckthorn cultivars bred in the Altai belong to the intensive-type genotypes: ‘Chuyskaya’ (5.22 t/ha; bi = 1.88), ‘Prevoskhodnaya’ (5.18 t/ha; bi = 1.55), ‘Obilnaya’ (5.09 t/ha; bi = 1.37), ‘Panteleevskaya’ (4.77 t/ha; bi = 1.51), and ‘Lyubimaya’ (4.16 t/ha; bi = 1.31). Their cultivation in Chelyabinsk Province is possible only with advanced agricultural practices.